Schwannoma of the Base of the Tongue: A Case Report of a Rare Disease and Review of Literatures - Mohd. Yusuf Haider; Manjur Rahim; N. M. K. Bashar; Md. Zakir Hossain; Sk Md Jaynul Islam (Case Reports in Surgery)
Background. Schwannoma is a benign nerve sheath tumor. It was first identified by Virchow in 1908. These tumors can emerge from any nerve covered with a Schwann cell sheath, including the cranial nerves (with the exception of the optic and olfactory nerves), the spinal nerves, and the autonomous nervous system (Harada H, Omura K and Maeda A, 2001). Case Presentation. A 28-year-old male farmer presented with a swelling at the right side of the base of tongue extending into the oral tongue. It was identified incidentally by his newly married wife while he was yawning. It was asymptomatic. The patient had no difficulty in chewing, swallowing, or phonation and also no sensory or taste abnormalities. The tongue movements were normal. Conclusions. Diagnosis of schwannoma should be considered for a smooth, painless, firm swelling in the tongue. A schwannoma of the tongue may grow large enough before producing any symptom. Around 25–40% of schwannoma happen within the head and neck region, and among these, 1-12% occurs in the oral cavity, most regularly the tongue or mouth floor. Schwannoma of the tongue does not show any age or sex predisposition. It usually presents as a painless lump in the tongue, but when it grows larger than 3.0 cm, it may produce dysphagia, pain, or discomfort and change in the quality of voice. Here, we report a case of large (4 cm×3 cm) asymptomatic schwannoma of the tongue in a 28-year-old male patient and review the literature available during the last 61 years.